2013
DOI: 10.1093/cid/cit747
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes by Sex Following Treatment Initiation With Atazanavir Plus Ritonavir or Efavirenz With Abacavir/Lamivudine or Tenofovir/Emtricitabine

Abstract: NCT00118898.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 13 publications
1
27
1
Order By: Relevance
“…Sex was not significantly associated with virologic failure, which was primarily in agreement with a study of time to virologic failure in the A5202 study by Smith et al. 19 In addition, there was no significant difference in outcome when evaluating history of IV drug use, the assigned NRTI backbone, and HIV-1 RNA stratification level at screening.…”
Section: Discussionsupporting
confidence: 87%
“…Sex was not significantly associated with virologic failure, which was primarily in agreement with a study of time to virologic failure in the A5202 study by Smith et al. 19 In addition, there was no significant difference in outcome when evaluating history of IV drug use, the assigned NRTI backbone, and HIV-1 RNA stratification level at screening.…”
Section: Discussionsupporting
confidence: 87%
“…The association of ABC with dyslipidemia has been reported in some studies; in the HEAT trial, ABC/3TC was associated with an increase in TC and TG at 96 weeks; however, glucose had no modification related to this backbone [16]. Another study, ACTG5202, found a higher frequency of dyslipidemia with ABC/3TC either with ATV/r or with EFV [17]. Finally, the ASSERT trial, found a statistically significant increase in TC and TG with ABC/LMV regimens compared with TDF/FTC in treatment-naïve infected patients [18].…”
Section: Regimen Tdf/ftc+efv Tdf/ftc+nvp Abc/3tc+lpv/r Abc/3tc+efv Abmentioning
confidence: 85%
“…Response to the ABC/3TC + ATV/r regimen has also undergone gender stratification analysis in the ACTG A5202 study 15. A5202 applied a more restrictive definition of virologic failure than ARIES and reported more virologic failures among the female than male subjects while they were receiving ABC/3TC + ATV/r over the 192-week randomization period (hazard ratio, 1.72 in multivariable analysis), although adherence was similar between genders.…”
Section: Discussionmentioning
confidence: 99%